Outcomes of Patients With Active Cancer and COVID-19 in the Intensive-Care Unit: A Multicenter Ambispective Study - Plais, Henri; Labruyère, Marie; Creutin, Thibault; Nay, Paula; Plantefeve, Gaëtan; Tapponnier, Romain; Jonas, Maud; Ngapmen, Nadege Tchikangoua; Le Guennec, Loïc; De Roquetaillade, Charles; Argaud, Laurent; Jamme, Matthieu; et al. (Frontiers in Oncology, 2022)
Background Whether patients with cancer are reported to harbor an increased susceptibility to SARS-CoV-2 infection, data in the intensive care unit (ICU) setting are scarce. Research question We aimed to investigate the association between active cancer and mortality among patients requiring ICU support. Study design and methods We did an ambispective cohort study at 17 hospitals in France. We included all adult active cancer patients with SARS-CoV-2 infection who needed support in the ICU. For each cancer patient, we included 3 non cancer patients. Mortality at day 60 after ICU admission was compared between cancer patients and non-cancer patients using a regression model with inverse probability weighting based on propensity score for cancer. Results Between March 12, 2020 and March 8, 2021, 2608 patients were admitted with SARS-CoV-2 infection in the 17 ICUs, accounting for 2.8 % of the total ICU population within the same period in France. Among them, 105 (n=4%) presented with cancer (51 patients had hematological malignancy and 54 patients had solid tumors). 409 of 420 patients were included in the propensity score matching process, of whom 307 patients in the non-cancer group and 102 patients in the cancer group. 145 patients (35%) died in the ICU at day 60, 59 (56%) with cancer and 86 (27%) without cancer. In the primary logistic regression analysis, the odds ratio for death associated to cancer was 2.3 (95%CI 1.24 – 4.28, p=0.0082) higher for cancer patients than for a non-cancer patient at ICU admission. Exploratory multivariable analyses showed that solid tumor (OR: 2.344 (0.87-6.31), p=0.062) and hematological malignancies (4.144 (1.24-13.83), p=0.062) were independently associated with mortality. Interpretation Patients who had cancer and required ICU support for SARS-CoV-2 infection had an increased mortality, hematological malignancy harboring the higher risk in comparison to solid tumor